Factors affecting woody plant species diversity of fragmented seasonally dry oak forests in the Mixteca Alta, Oaxaca, Mexico - María de los Remedios Aguilar-Santelises; Rafael F. del Castillo (Revista Mexicana de Biodiversidad)
We explored the relationship between fragment area, topographic heterogeneity, and disturbance intensitywith tree and shrub species diversity in seasonally dry oak forest remnants in the Mixteca Alta, Oaxaca, Mexico. Thefragments are distributed in a matrix of eroded lands and crop fields, have a complex topography, and are disturbedby plant extraction and trail opening. Sampling was conducted in 12 fragments from 12-3 211 ha. Topographicheterogeneity was estimated by the fragment’s standard deviation in slope-aspect, slope, and altitude. The density ofstumps and roads were used as estimators of disturbance intensity. Fisher’s α diversity ranked from 0.95 to 4.55 for thetree layer; and 2.99 to 8.51, for the shrub layer. A structural equation model showed that the diversity of woody plantsincreases with topographic heterogeneity and disturbance in the remnants. When these 2 variables were considered,diversity tended to decrease with fragment size probably because smaller fragments have a greater perimeter-to-arearatio and therefore proportionally offer more opportunities for pioneer species colonization. Indeed, the tree-to shrublayerdiversity ratio increased with fragment size. Conservation strategies in fragmented forests must consider thefragment´s environmental heterogeneity, the disturbance type and intensity, and the species to be preserved.